Performance evaluation of the Access HBsAg and Access HBsAg confirmatory assays on the DxI 9000 Access Immunoassay Analyzer - Benoit Visseaux; Jérémie Gautier; Françoise Le Boulaire; Catherine Coignard; Claire Vincent; Sandrine Gréaume; Isabelle Voisin; Veronique Lemée; Jean-Christophe Plantier; Yves-Edouard Herpe; Etienne Brochot; Stephanie Bord; et al. (Practical Laboratory Medicine, 2024)
Introduction: This study evaluated the clinical and analytical performances of the Access HBsAg and the Access HBsAg Confirmatory assays on the DxI 9000 Access Immunoassay Analyzer (Beckman Coulter, Inc.). Materials and methods: Diagnostic specificity and sensitivity of the Access HBsAg and Access HBsAg Confirmatory assays were evaluated by comparing the Access assays to the final HBsAg sample status determined using the Architect, PRISM, or Elecsys HBsAg assays, along with Architect or PRISM HBsAg Confirmatory assays. Imprecision, sensitivity on seroconversion panels, analytical sensitivity on WHO, and recognition of HBV variants were also evaluated. Results: A total of 7534 samples were included in the analysis (6047 blood donors, 1032 hospitalized patients, 455 positive patients’ samples). Access HBsAg assay sensitivity and specificity were at 100.00% (99.19–100.0) and 99.92% (99.82–99.97), respectively. Sensitivity of Access HBsAg Confirmatory assay was 100.00% (99.21–100.0) on the 464 HBsAg positive samples. The use of a high positive algorithm for the Access HBsAg assay, wherein samples with S/CO ≥ 100.00 were considered positive without requiring repeat or confirmatory testing, was successfully evaluated with all 450 specimens with S/CO greater than 100.00 (sensitivity 100.00%; 99.19–100.0). Access HBsAg assay demonstrated good analytical performance, equivalent recognition of seroconversion panels compared to Architect assay, and an analytical sensitivity between 0.022 and 0.025 IU/mL. All HBV genotypes, subtypes and mutants were well detected without analytical sensitivity loss. Conclusion: Access HBsAg and Access HBsAg Confirmatory assays demonstrated robust performances. They provide low samples volume requirements and a simplified process, no systematic retesting for high positive samples.